Pengaruh Manajemen Laba, Komite Audit, Kepemilikan Institusional dan Corporate Social Responsibility Disclosure terhadap Agresivitas Pajak - Ardan Gani Asalam; Anisa Putri Astuti (Jurnal Informatika Ekonomi Bisnis, 2023)
Taxes make a major contribution to the State Budget (APBN) by contributing the largest revenue. However, the realization of tax revenue in Indonesia in the 2019-2021 period tends to decline due to obstacles in tax collection, namely tax aggressiveness. This study aims to determine the effect of profit management, audit committee, institutional ownership, and corporate social responsibility disclosure on tax aggressiveness. The population in this study is primary consumer goods sector companies listed on the Indonesia Stock Exchange for the 2019-2021 period. The sampling technique used in this study was purposive sampling technique, then obtained 25 companies with a research period of three years so that the number of research samples was 75 data. The data analysis method used in this study is panel data regression analysis. The results showed that profit management, audit committee, institutional ownership, and CSRD simultaneously influence tax aggressiveness. Partially, profit management, institutional ownership, and CSRD positively affect tax aggressiveness, and audit committees negatively affect tax aggressiveness. This research can contribute to science, especially taxation. Researchers can then use this study as a reference for further research on tax aggressiveness and the factors that influence it.